2019
DOI: 10.3889/oamjms.2019.292
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Presepsin in Patients with Acute Surgical Diseases

Abstract: AIM: The purpose of this study was to determine the level of significance of markers in the development of intra-abdominal hypertension in patients with acute surgical diseases of the abdominal cavity. METHODS: The authors surveyed 100 patients who were monitored at the Regional Clinical Hospital, Karaganda. The criterion for inclusion in the study was the informed consent of patients to participate in the study, the presence of acute surgical pathology, and the monitoring of intra-abdominal pressure ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…These studies demonstrated that presepsin was a sensitive and specific predictor for the development of sepsis in abdominal organs, leading the authors to conclude that presepsin could be utilized as a diagnostic marker. [18,19] In this study, the cutoff value for presepsin in patients with acute cholecystitis was found to be 134. Oxidative stress responses, marked by a balance between prooxidants and antioxidants, are crucial aspects of the body's response to surgical stress and the activation of inflammatory cells.…”
Section: Discussionmentioning
confidence: 60%
“…These studies demonstrated that presepsin was a sensitive and specific predictor for the development of sepsis in abdominal organs, leading the authors to conclude that presepsin could be utilized as a diagnostic marker. [18,19] In this study, the cutoff value for presepsin in patients with acute cholecystitis was found to be 134. Oxidative stress responses, marked by a balance between prooxidants and antioxidants, are crucial aspects of the body's response to surgical stress and the activation of inflammatory cells.…”
Section: Discussionmentioning
confidence: 60%
“…The main conclusion based on the analysis of the study results is that stenting and balloon angioplasty of the arteries of the lower extremities in cases of purulent and necrotic complications of DFS can reduce the number of repeated minor interventions and foot amputations 3.8 times and the frequency of hip disarticulations 6 times as well as preserve the weightbearing ability of the feet in 94.2% of patients ( 14 , 15 ). Endovascular interventions, stenting, and balloon angioplasty, on 1 of the tibial arteries only show encouraging positive treatment outcomes, and therefore is sufficient in terms of the number of arteries required for the intervention to obtain the expected result.…”
Section: Discussionmentioning
confidence: 95%
“…In a clinical study of patients with acute surgical pathology, including acute intestinal obstruction, some correlation has been found between an increase in intraabdominal pressure and an increase in the level of presepsin. Moreover, some researchers found that presepsin can be used to stratify the risk of abdominal sepsis [62].…”
Section: Bacterial Translocation Detection Methodsmentioning
confidence: 99%